The Integrated Diversity Education Approach in Pesantren (IDEA–P Model): Reconstructing Multicultural Islamic Pedagogy for Inclusive Civilization - Islam, Muhammad Hifdil (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2025)
This paper proposes a new theoretical frameworkthe Integrated Diversity Education Approach in Pesantren (IDEA–P Model as a response to the growing need for structured diversity education within Indonesia’s Islamic boarding schools (pesantren). Drawing from 30 interdisciplinary studies on multiculturalism, inclusive pedagogy, and Islamic leadership, this study synthesizes existing approaches into a unified model grounded in Islamic theological, pedagogical, and social principles. The IDEA–P framework consists of three interrelated axes: the Spiritual Axis, emphasizing divine unity and compassion (tawhid and rahmah); the Pedagogical Axis, centered on dialogical and differentiated learning; and the Social Axis, focusing on multicultural leadership and institutional inclusivity. These axes are operationalized through five structural components epistemic integration, dialogical pedagogy, inclusive curriculum design, multicultural leadership, and reflective evaluation. The model positions pesantren as transformative moral communities that balance tradition and modernity, theology and pluralism, faith and civic responsibility. This study contributes a conceptual foundation for advancing diversity education in Islamic contexts, offering both theoretical depth and practical implications for educators, policymakers, and scholars